Integrin beta-3 genetic variants and risk of venous thromboembolism in colorectal cancer patients. Issue 5 (November 2015) - Bianconi, Daniela; Schuler, Alexandra; Pausz, Clemens; Geroldinger, Angelika; Kaider, Alexandra; Lenz, Heinz-Josef; Kornek, Gabriela; Scheithauer, Werner; Zielinski, Christoph C.; Pabinger, Ingrid; Ay, Cihan; Prager, Gerald W.
Abstract: Background: Integrin β3 is involved in tumor and endothelial cell biology as well as in platelet aggregation. Herein, we evaluated the predictive potential of three germline single nucleotide polymorphisms (SNPs) in the integrin β3 gene (rs3809865, rs5918 and rs4642) to predict the risk of venous thromboembolism (VTE) in colorectal cancer (CRC) patients, which is one of the leading causes of death among cancer patients. Methods: 112 patients diagnosed with CRC enrolled in the prospective Vienna Cancer and Thrombosis Study (CATS) were assessed with a median follow-up of 46 months. DNA was isolated from venous blood samples and SNPs were analyzed by the PCR-RFLP method. Results: VTE occurred in 12% (n = 13) of all patients. The SNPs rs5918 and rs4642 were not associated with VTE risk. For rs3809565, 23% (n = 11) of patients had the A/A genotype, 4% (n = 2) had the A/T genotype, but none (0%) had the T/T genotype. In the univariate analysis, patients with the A/A genotype had a significantly higher risk to develop VTE compared to the other polymorphisms ( P  = 0.0005 after Fine and Gray). In the multivariable analysis, the predictive value remained significant. Conclusions: This study identified the rs3809865 A/A genotype as an independent risk factor for VTE in CRC patients. Our findings would help identify high risk patients and would be essential for tailored anticoagulant prophylaxis. Highlights: Integrin β3 plays an important role in thrombosis. Venous thromboembolism (VTE) is one of the leading causes of death in cancer. A correlation between SNPs of integrin β3 and risk of VTE in colorectal cancer is proposed. The rs3809865 A/A genotype represents an independent risk factor to develop VTE.